2016
DOI: 10.1016/j.yqres.2015.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of mylodontid sloths and insights on their potential distributions during the late Pleistocene

Abstract: Species distribution models (SDMs) for the last interglacial (LIG), the global last glacial maximum (LGM) and the Holocene climatic optimum (HCO) were generated for three extinct South American Pleistocene mylodontid giant sloths, Glossotherium robustum, Lestodon armatus and Mylodon darwinii. They are recorded co-occurring in some localities including Arroyo del Vizcaíno site (AdV) in Uruguay. Co-occurrence records were studied based on the overlap of their generated areas of potential distributions, and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…Although both data types, bioclimatic layers and occurrence records, are important to estimate the model, the final predicted distribution is made by projecting the model onto the bioclimatic layers (Elith and Leathwick, 2009). This approach has been extensively applied in ecology, biogeography and conservation biology for studying the distribution of extant species (Elith and Leathwick, 2009; Hao et al, 2019), and more recently in paleontology (e.g., Varela and Fariña, 2016; Villavicencio et al, 2019). However, beyond its potential utility for the study of the distribution of species in the past and the growing availability of detailed paleo-bioclimatic reconstruction (Brown et al, 2018; Fordham et al, 2017), species distribution models have not been widely employed in archaeology to estimate the distribution of main human prey (for an exception see Politis et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both data types, bioclimatic layers and occurrence records, are important to estimate the model, the final predicted distribution is made by projecting the model onto the bioclimatic layers (Elith and Leathwick, 2009). This approach has been extensively applied in ecology, biogeography and conservation biology for studying the distribution of extant species (Elith and Leathwick, 2009; Hao et al, 2019), and more recently in paleontology (e.g., Varela and Fariña, 2016; Villavicencio et al, 2019). However, beyond its potential utility for the study of the distribution of species in the past and the growing availability of detailed paleo-bioclimatic reconstruction (Brown et al, 2018; Fordham et al, 2017), species distribution models have not been widely employed in archaeology to estimate the distribution of main human prey (for an exception see Politis et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Species distribution is modeled using a maximum entropy approach ( maxent ; Phillips et al, 2006, 2017), which uses environmental layers or bioclimatic raster files and geo-referenced occurrence records to estimate a model that predicts the suitability conditions for the species presence in each raster pixel (Hijmans et al, 2017). We employ this approach because is widely used in paleoecology (e.g., Politis et al, 2011; Varela and Fariña, 2016; Villavicencio et al, 2019) and is considered one of the most effective methods for species distribution modeling with presence-only data (Elith et al, 2010; Espinosa et al, 2018; Phillips et al, 2006; Politis et al, 2011). Additionally, we explore the spatial variation in the importance of guanaco for human diet in Patagonia during the end of the Late Pleistocene and the main time periods of the Holocene.…”
Section: Introductionmentioning
confidence: 99%
“…Like the vast majority of the Pleistocene megafauna, M. darwinii went extinct at the Pleistocene/Holocene boundary, approximately 10 000 years ago [ 2 ]. Numerous subfossils of M. darwinii have been found across the South American southern cone [ 3 ], including the famous Mylodon Cave (Cueva del Milodón, Ultima Esperanza, Chile). This cave derives its name from the numerous and exquisitely preserved remains of this ground sloth found inside.…”
Section: Introductionmentioning
confidence: 99%
“…1). The largest mylodontid Lestodon armatus was selected because it is probably the most abundant ground sloth found in Pleistocene deposits of Uruguay (Fariña et al 2014, Varela andFariña 2016), along with the large number of remains found in Argentina and Brazil, and because, despite this, it remains relatively little studied. We also collected data from sloth genera covering all sloth families from a revision of the literature, as well as published images and measurements of museum specimens (Tab.…”
Section: Taxon Sampling and Data Acquisitionmentioning
confidence: 99%